2020
DOI: 10.1111/infa.12372
|View full text |Cite
|
Sign up to set email alerts
|

Experience with research paradigms relates to infants’ direction of preference

Abstract: Interpreting and predicting direction of preference in infant research has been a thorny issue for decades. Several factors have been proposed to account for familiarity versus novelty preferences, including age, length of exposure, and task complexity. The current study explores an additional dimension: experience with the experimental paradigm. We re-analyzed the data from 4 experiments on artificial grammar learning in 12-month-old infants run using the Head-turn Preference Procedure (HPP). Participants in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…Thus, prior experience with the task, and the touchscreen paradigm, had long-lasting beneficial effects on reaction times when performing the task for the second time. The effect of prior experience with the task varied across ages and ranged between 0.18 and 0.68 s. A very recent study has similarly reported that experience with paradigms affects infants' behavior in the task: e.g., more experience with the head-turn preference paradigm (more lab visits) leads to smaller familiarity preference, i.e., smaller effect sizes, suggesting that prior experience with the task cumulates and modulates the learning outcome (Santolin, Garcia-Castro, Zettersten, Sebastian-Galles, & Saffran, 2021).…”
Section: Processing and Reaction Timesmentioning
confidence: 91%
“…Thus, prior experience with the task, and the touchscreen paradigm, had long-lasting beneficial effects on reaction times when performing the task for the second time. The effect of prior experience with the task varied across ages and ranged between 0.18 and 0.68 s. A very recent study has similarly reported that experience with paradigms affects infants' behavior in the task: e.g., more experience with the head-turn preference paradigm (more lab visits) leads to smaller familiarity preference, i.e., smaller effect sizes, suggesting that prior experience with the task cumulates and modulates the learning outcome (Santolin, Garcia-Castro, Zettersten, Sebastian-Galles, & Saffran, 2021).…”
Section: Processing and Reaction Timesmentioning
confidence: 91%
“…Work directly aimed at improving infant behavioral methods is complemented by other methodologically-related research. For example Santolin et al (2020) recently reported evidence that infants' experience with a paradigm is related to the direction of preference they show (i.e. whether infants attend more when they hear novel versus familiar stimuli).…”
Section: Solution 3: Develop Better Infant Paradigmsmentioning
confidence: 99%
“…Work directly aimed at improving infant behavioral methods is complemented by other methodologically-related research. For example Santolin et al (2020) recently reported evidence that infants' experience with a paradigm is related to the direction of preference they show (i.e. whether infants look more to novel or familiar stimuli).…”
Section: Solution 3: Develop Better Infant Paradigmsmentioning
confidence: 99%